The Cadre Empowerment and Education for Pregnant Women and Toddler Mothers in Efforts to Prevent Stunting in Sukamaju, Jambi Luar Kota, Muaro Jambi - Neni Heryani; Herinawati; Murdayah (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Sukamaju Village is the village with the highest incidence of stunting in the Pondok Meja Health Center working area, 31%. Stunting in Muaro Jambi Regency experienced an increase of 5.1% from 2016 of 25.5% to 30.6% in 2017. The aim of the activity is to empower cadres by teaching cadres to be able to provide education using flip-sheet media containing about stunting to pregnant women and mothers with toddlers. Stunting-themed educational activities were carried out for 40 cadres. This activity is carried out directly using a flip sheet containing stunting including the meaning of stunting, recognizing the signs of stunting, preventing stunting, causes of stunting, the impact of stunting, as well as tips for preventing stunting during the first 1000 days of life (HPK). The educational activities went well and received a good response and enthusiasm from the cadres. This is demonstrated by the cadres' enthusiasm in asking questions and sharing information obtained from learning outcomes using flip-sheet media. The education provided was also conveyed well as shown by the increase in cadres' knowledge regarding stunting by looking at the comparison of pre-test and post-test results which increased significantly. For this reason, educational activities using flip-sheet media need to continue to be implemented as an effort to increase cadres' knowledge in educating pregnant women and mothers with toddlers.